Situation Report: Poland, 27 August 1971 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Relations between Workers and Party: The Situation in the Gdansk Shipyards, in Katowice Voivodship [Voivodeship] Coverage of Romania Affairs Comments on the Berlin Agreement State of the Economy at the End of July 1971 First Nuclear Power Station to Be Built US Approves Sale of Vital Oil Refinery Equipment to Poland Two Communiqués on Causes of Air Disaster, Oil Refinery Fire